Cyclic cRGDfk peptide and Chlorin e6 functionalized silk fibroin nanoparticles for targeted drug delivery and photodynamic therapy. (April 2018) - Mao, Baiping; Liu, Caixia; Zheng, Wenwen; Li, Xiaoheng; Ge, Renshan; Shen, Haifa; Guo, Xiaoling; Lian, Qingquan; Shen, Xian; Li, Chao
Abstract: Regenerated silk fibroin (SF) is a natural biomacromolecule with excellent biocompatible and biodegradable properties. In this study, cyclic pentapeptide cRGDfk and Chlorin e6 (Ce6) were conjugated to SF polypeptides, and genipin was used to prepare 5-fluorouracil (5-FU) doped SF-based nanoparticles (NPs). The photodynamic therapy (PDT) potential and active targeting properties were systematically investigated in αv β3 integrin receptor over-expressed MGC-803 cells in vitro. The results revealed that treatment with the multifunctional SF-based NPs and PDT, high level of reactive oxygen species (ROS) and cell death can be induced in MGC-803 cells. Combine with PDT, the in vivo antitumor effect of the SF-based NPs was evaluated in gastric cancer xenograft mice model. The results demonstrated that the SF-based NPs had ideal active tumor targeting property and the tumor burden can be reduced noticeably. Furthermore, the organs of mice in SF NPs treatment groups did not show obvious toxicity, demonstrating good biocompatibility and security profiles of SF NPs in vivo. Overall, our results suggest that the SF-based NPs are promising drug delivery carriers, together with PDT, the multimodality therapy could be potential regimen in future clinical cancer treatment. Graphical abstract: The cRGDfk and Chlorin e6 conjugated Silk fibroin (SF) based nanoparticles (SF NPs) were fabricated for targeted drug (5-FU) delivery and photodynamic therapy (PDT). The SF NPs manifested sustained release, active tumor cell targeting, perfect PDT potentials, and reduced the tumor burden greatly in vivo with excellent biocompatibility and safety. Highlights: cRGDfk and Chlorin e6 conjugated SF-based NPs were fabricated for targeted drug delivery and photodynamic therapy (PDT). The SF-based NPs manifested sustained release, active tumor cell targeting, and perfect PDT potentials in MGC-803 cells. Together with PDT, the SF-based NPs reduced the tumor burden greatly with excellent biocompatibility and safety in vivo.